1996
DOI: 10.1002/j.1460-2075.1996.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical chaperones interfere with the formation of scrapie prion protein.

Abstract: The fundamental event in prion diseases involves a conformational change in one or more of the alpha‐helices of the cellular prion protein (PrP(C)) as they are converted into beta‐sheets during the formation of the pathogenic isoform (PrP(Sc)). Here, we show that exposure of scrapie‐infected mouse neuroblastoma (ScN2a) cells to reagents known to stabilize proteins in their native conformation reduced the rate and extent of PrP(Sc) formation. Such reagents include the cellular osmolytes glycerol and trimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
218
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(225 citation statements)
references
References 69 publications
5
218
1
1
Order By: Relevance
“…Solid media contained 2.3% agar (Difco). Mouse neuroblastoma (N2a) cells (31) were cultured as described previously (32). PrP was detected by the monoclonal anti-PrP antibody 3F4 (33) or the polyclonal anti-PrP antiserum A7 (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid media contained 2.3% agar (Difco). Mouse neuroblastoma (N2a) cells (31) were cultured as described previously (32). PrP was detected by the monoclonal anti-PrP antibody 3F4 (33) or the polyclonal anti-PrP antiserum A7 (10).…”
Section: Methodsmentioning
confidence: 99%
“…Western Blotting-Following SDS-PAGE, proteins were transferred onto a nitrocellulose membrane and analyzed as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…One example of this is the effect of the 'chemical chaperone' trimethylamide N-oxide (TMAO) on PrP misfolding. Experimentally, it was found that addition of TMAO efficiently reduced PrP Sc formation in mouse neuroblastoma cells (75% reduction with 120 mM TMAO) [167]. Simulations in the presence of 1M TMAO were performed with hamster recPrP (res.…”
Section: The Effect Of Small Molecule Ligandsmentioning
confidence: 99%
“…43 and 44). Several in vitro and cell culture studies revealed that chaperones have an impact on the conversion of the prion protein and the aggregation of polyglutamine proteins (45)(46)(47)(48)(49)(50)(51)(52)(53)(54). The potential of chaperones in preventing or reducing the toxicity of misfolded proteins has finally been established in animal models showing that increased expression of Hsp70 and Hsp40 suppressed the toxicity of ␣-synuclein and polyglutamine proteins (55)(56)(57)(58)(59).…”
Section: Inactivation Of a Pathogenic Parkin Mutant By Spontaneousmentioning
confidence: 99%